Pelaksanaan Hukuman Di Pondok Pesantren Darussalam Kasomalang Subang - Ni’mawati; Andewi Suhartini; Nurwadjah Ahmad EQ (STAI Siliwangi Bandung, 2022)
This study aims to analyze the implementation of punishment in the Islamic boarding school Darussalam Kasomalang, Subang. This study uses a qualitative approach. While the use method is descriptive-analytical, they describe the implementation of punishment at Pesantren Darussalam Kasomalang Subang. The results of this study are: 1) The executor in giving the first sanction is the mudabbir, who is responsible for the tsanawiyah level students. The second is munadzdzim, responsible for the regulations of the pesantren. They are responsible for all students, including providing sanctions for students and mudabbir who violate. 2) several forms of punishment are less educational, namely physical violence by hitting the thigh. Some penalties are destructive so that it causes futility, namely damaging HP. 3) Lack of supervision over the implementation of sanctions can lead to irregularities. Giving sanctions should not be in the form of violence and in vain because it leads to actions that are not educational. Making more useful sanctions such as additional memorization tasks or fines is necessary.